KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING DIABETES IN THE GENERAL POPULATION OF PAKISTAN - IJAZ , S; NAEEM , N; HAIDER , A; AJAZ , S; SATTAR , S; DEVI , J (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the knowledge, attitudes, and practices related to diabetes in the general population. A cross-sectional study was conducted involving 300 participants. Data was collected through structured interviews using a standardized questionnaire. The questionnaire included demographic information, awareness of diabetes and its risk factors, general knowledge about diabetes and common eye diseases, and practices related to diabetes management. The results revealed a significant knowledge gap among the participants regarding diabetes and its risk factors. A considerable proportion of the general population demonstrated limited knowledge about the disease. Socio-economic disparities were observed, with individuals of higher education and socio-economic status exhibiting better knowledge and awareness of diabetes. Age was also associated with knowledge levels, with younger individuals displaying higher knowledge levels than older age groups. This study highlights the urgent need for targeted educational interventions to bridge the knowledge gap regarding diabetes in the general population. Efforts should be directed towards reaching individuals with lower education and socio-economic status. Addressing the knowledge gap, particularly among vulnerable populations, can improve diabetes management and health outcomes.